Happy Birthday Marlboro: the cigarette whose taste outlasts its customers. Issue 2 (24th March 2006) - Hyland, A; Goldstein, R; Brown, A; O'Connor, R; Cummings, K M
Abstract : Marlboro is 50 years old—and still killing its customers